STN Versus GPi Deep Brain Stimulation for Action and Rest Tremor in Parkinson’s Disease - Wong, Joshua K.; Viswanathan, Vyas T.; Nozile-Firth, Kamilia S.; Eisinger, Robert S.; Leone, Emma L.; Desai, Anuj M.; Foote, Kelly D.; Ramirez-Zamora, Adolfo; Okun, Michael S.; Wagle Shukla, Aparna (Frontiers in Human Neuroscience, 2020)
Objective: To investigate the effects of subthalamic (STN) and globus pallidus internus (GPi) deep brain stimulation (DBS) on individual action tremor/postural tremor (AT) and rest tremor (RT) in Parkinson’s disease (PD). Randomized DBS studies have reported marked benefit in tremor with both GPi and STN DBS, however there is a paucity of information available on AT vs RT when separated by the surgical target. Methods: We retrospectively reviewed the 1-year clinical outcome of PD patients treated with STN and GPi DBS at the University of Florida. We specifically selected patients with moderate to severe AT. Eighty-eight patients (57 STN and 31 GPi) were evaluated at 6 and 12 months for changes in AT and RT in the OFF-medication/ON stimulation state. A comparison of “response” was performed and defined as greater than or equal to a 2-point decrease in tremor score. Results: STN and GPi DBS both improved AT at 6- and 12-months post-implantation (p<0.001 and p<0.001). The STN DBS group experienced a greater improvement in AT at 6 months compared to the GPi group (p=0.005) but not at the 12 months follow-up (p=0.301). Both STN and GPi DBS also improved RT at 6- and 12-months post-implantation (p<0.001 and p<0.001). There was no difference in RT scores between the two groups at 6 months (p=0.23) or 12 months (p=0.74). The STN group had a larger proportion of patients who achieved a “response” in AT at six months (p<0.01), however this finding was not present at 12 months (p=0.23). A sub-analysis revealed that in RT, the STN group had a larger percentage of “responders” when followed through 12 months (p < 0.01). Conclusion: Both STN and GPi DBS reduced PD associated AT and RT at 12 month follow-up. There was no advantage of either brain target in the management of RT or AT. One nuance of the study was that STN DBS was more effective in suppressing AT in the early postoperative period, however this effect diminished over time. Clinicians should be aware that it may take longer to achieve a similar tremor outcome when utilizing the GPi target.